Correlation of Concept and Image in the Process of Algorithm development for Analyzing the Image-Concept of a State - Ksenia P. Posternyak; Kirill P. Posternyak (Vestnik Rossijskogo universiteta družby narodov. Seriâ: Teoriâ âzyka, semiotika, semantika (Online), 2024)
The article is topical due to the interest of scientists to the images of states as subjects of politics and their formation and transformation in political discourse. The article contains the theoretical substantiation of the use of the term “image-concept” and offers the algorithm for analyzing linguistic material in synchrony and diachrony. Using this algorithm we describe the means of verbalization of 4 layers of the image-concept “Russia” in the British media discourse of 1916-1922, the period crucial for our country. Thus, we reveal the range of nominations, means of evaluation, metaphors as well as associations formed by British journalist in texts devoted to Russia.